The management of scientific-methodological work in the institutions of technical and professional education in Cuba - Ramírez Lahera, Lina Margarita; González Ramírez, Jorge (Avances en Supervisión Educativa, 2017)
This work deals with a complex of research which has been done on the management of the methodological scientific work in the institutions of the polytechnical education in Cuba. It is related to the necessity of its progress and development just to get better results in the scientific preparation of the teachers, their development and self development to high the quality of the educative. Teaching process, taking into account the new changings of the methodological work rules, that states the methodological scientific work as one of the two directions of the methodological work developed in Cuban Educational Ministry.
Keywords: direction; scientific methodological work; polytechnical education